Potential of Postharvest Extension Service Delivery in Reducing Food Losses: A Study of Two Periodic Markets in the Eastern Region of Ghana - Vida Opoku Edusei; William Odoom; Yaw Gyau Akyereko; Araba Dhailly Arkorful; Ryan Kusi Osei-Asibey; Maxwell Adu; John Owusu (AgroEnvironmental Sustainability)
This study assessed the current status and potential of postharvest extension in reducing food losses at the Adawso and Asesewa periodic markets in the Eastern Region of Ghana. A survey utilizing direct face-to-face questionnaire interviews to obtain data and information was undertaken on 167 marketers in the two markets by simple random sampling. The results revealed that trading at the two markets was dominated by women (96.4%) mostly of a mixed age group of the youth and middle-aged (72.0%) with the majority (67%) having primary and junior secondary levels of education. Most marketers (71.2%) reported more than 10% postharvest food losses and had no access to postharvest extension services (85.6%) and information on postharvest technologies for food loss prevention or reduction (88.6%). However, marketers were willing to participate in postharvest training (86.6%) and adopt new food loss prevention technologies (85%). Probit regression analysis identified marketers’ education level and access to postharvest extension as significant predictors of their perception of postharvest extension contribution to food loss prevention in the markets. Each additional unit of education increases the likelihood of perceiving postharvest extension as beneficial by 1.21, similarly, access to postharvest extension increases the likelihood by 1.1 times. This implies that education and access to postharvest extension services are significant factors in food loss prevention and reduction. The study therefore suggests that provision of the services in the markets that include practical demonstrations and hands-on training presents a valuable opportunity for food loss reduction to promote sustainability.